Pengembangan Aplikasi Kasir Menggunakan Model Waterfall - Aji Saputra; Cut Fera Inong Safitri; Fitriyani Fitriyani; Yarni Gulo; Teti Desyani (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2021)
Many companies engaged in printing services still use manual processes in their transactions, the system process is less efficient and the possibility of errors in input data can still occur. Like the process of recording orders using paper, calculations using calculators and sales transactions written on books. Therefore, for these problems, a cashier application is needed that can facilitate the order process, calculations and transactions accurately with a web-based cashier application that features login, sales transactions, product data, add products, settings and exit applications. Our development process uses the waterfall method and to describe the system design we use the Unified Modeling Language (UML). Application using the waterfall method can make it easier to complete the application development process because there are already stages in the method.